Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm trying to prove that the primes with form $3k+1$ are not Eisenstein prime. This step: to find $a$ such that $a^2-a\equiv -1\pmod p$ when $p$ is a prime with $p\equiv 1\pmod 3$ is the only obstacle now, and I have thought of many methods, but none of them work.

I know that when proving prime of form $p=4n+1$ aren't Gaussian primes, we need $a$ such that $a^2 \equiv -1\pmod p$. This can be obtained by Wilson's theorem, that $(4n)!\equiv -1\pmod p$, which gives $(4n)!\equiv(1\times 2\times \cdots \times(2n))((-2n)\times\cdots\times(-2)\times(-1))=(1\times 2\times \cdots \times(2n))^2\pmod p$. And this constructs the $a$ we want.

But in this case, things are different. I've tried via mathematica, that the $(3k)!$ or $(6m)!$ cannot be factorized into $a(a-1)$. Such as $720=24\times30$. But when I minus some multiple of the primes, it becomes $24\times 23\equiv-1(\mod 7)$. This special case can't give me more details. So I wonder if there is some method to find $a$ or prove existence without finding it? Only hints are needed! Thanks!

share|cite|improve this question
$$a^2-a\equiv-1\pmod p\iff (2a-1)^2\equiv-3\pmod p\implies \left(\frac{-3}p\right)=1$$ Check here ( when $-3$ is a QR of $p$ – lab bhattacharjee Oct 15 '13 at 14:55
Solving $a^2-a\equiv -1\bmod p$ by the quadratic equation leads to the consideration of whether $-3$ is a quadratic residue $\bmod p$. What is the Legendre symbol $(-3|p)$? – lhf Oct 15 '13 at 14:55
up vote 1 down vote accepted

If $p \equiv 1 \bmod 3$, then you can form the polynomial $X^{(p-1)/3} - 1$ which has the zero $1$. Therefore, in $F_p$, $$X-1 \mid X^{(p-1)/3} - 1 \; \Rightarrow \; X^3 - 1 \mid X^{p-1} - 1.$$ On the other hand, $X^{p-1}-1$ decomposes as $(X-1) \cdot (X-2) \cdot ... \cdot (X-(p-1))$ by Fermat's little theorem.

Therefore $X^3 - 1$ splits into linear factors. Since $X^2 + X + 1$ divides $X^3 - 1$, it also splits into linear factors $X^2 + X + 1 = (X-a)(X-b)$. This gives you your $a$.

share|cite|improve this answer

We know $Y^3-1 = (Y-1)(Y^2-Y+1)$. Since $Y^3-1$ divides $Y^{p-1}-1$, it must have three distinct roots. Two of those roots must be roots of $Y^2-Y+1$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.